PRELIMINARY PHYSICAL AND SPECIAL TRAINING INDICATORS OF 11-12-YEAR-OLD FOOTBALL PLAYERS (World Bulletin of Physical Education and Sports Science, 2026)
The article presents methods for improving the physical fitness and developing the physical qualities of 11–12-year-old football players through various games. Physical changes in children were analyzed using the “Square” and “Envelope” exercises. The analysis results were divided into experimental and control groups and presented in tables. Conclusions were drawn based on the analysis of the results shown in the tables.
Keywords: Skill, ability, sports training, physical exercises, physical qualities, “Square”, “Envelope”, technique, tactics.